Effectiveness of functional exercises on pain and sleep quality in patients with primary dysmenorrhea: a randomized clinical trial - Kirmizigil, Berkiye; Demiralp, Cisel (Springer Heidelberg, 2020)
Purpose Primary dysmenorrhea is the most common gynecological problem in young women and adolescents. Exercise therapy provides positive effects on women with primary dysmenorrhea. The aim of the study was to investigate the effects of a combined exercise program on pain, sleep and menstrual symptoms in patients with primary dysmenorrhea. Methods The study is a randomized controlled study. The study included 28 sedentary individuals. The participants were assigned to two groups as the exercise (mean age 22.9 +/- 2.0 years) and the control (mean age 23.1 +/- 1.8 years) groups. The exercise protocol was carried out with the exercise group three times a week for eight weeks. The Visual Analog Scale (VAS) was used for assessing the intensity of pain. The Menstrual Symptom Questionnaire (MSQ) and Pittsburgh Sleep Quality Index (PSQI) were used for evaluating menstrual symptoms and sleep quality, respectively. The study was registered on the Clinical Trials website by the number NCT03625375. Results The comparisons between the groups revealed statistically significant differences in abdominal pain severity, MSQ total score and the subscale scores of negative outcomes and management methods (p < 0.05). The intragroup comparisons of the exercise group demonstrated that the scores of the low back pain and abdominal pain and the MSQ and PSQI scores were found to be significantly different after the 8-week program (p < 0.05). Conclusion The combined exercise therapy is an effective way to manage symptoms associated with primary dysmenorrhea.
Keywords: Dysmenorrhea; Exercise; Sleep; Menstrual cycle pain